Reconstructing Tawhid: Tawhid as the Foundation of Social Reform (An Analysis of Ibn Taymiyyah's Thought in the Contemporary Context) - Baidlawi Bukhari; Siswanto; Atiqullah (International Journal of Technology and Education Research, 2026)
This study examines Ibn Taymiyyah's concept of tawhid and explores its reconstruction as a foundation for social reform in the contemporary context. Although tawhid has traditionally been discussed within theological discourse, its broader social, moral, and political implications remain highly relevant for addressing contemporary challenges such as social injustice, corruption, declining public integrity, and moral crises. This research employs a qualitative normative approach using library research. Primary data are derived from Ibn Taymiyyah's principal works, while secondary sources include scholarly books and peer-reviewed journal articles. Data were collected through document analysis and interpreted using content analysis and a hermeneutic approach. The findings demonstrate that Ibn Taymiyyah conceptualizes tawhid as a comprehensive ethical framework encompassing the dimensions of rububiyyah, uluhiyyah, and asma' wa al-sifat. Beyond its theological significance, tawhid functions as a normative foundation for justice, accountability, ethical governance, and social solidarity. Reconstructing this concept provides an Islamic ethical paradigm capable of promoting social transformation and responding effectively to the moral, social, and political challenges faced by contemporary Muslim societies. Keywords: Tawhid; Ibn Taymiyyah; Social Reform; Islamic Ethics; Contemporary Islamic Thought